2015
DOI: 10.1016/j.cattod.2015.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sulfation and desulfation on NO reduction using Cu-chabazite SCR catalysts

Abstract: a b s t r a c tThis bench reactor study investigates the impact of gaseous sulfur on the NO x reduction activity of Cuchabazite SCR (Cu-CHA) catalysts at SO 2 concentrations representative of marine diesel engine exhaust. After 2 h of 500 ppm SO 2 exposure at 250 and 400 • C in the simulated diesel exhaust gases, the NO x reduction activity of the sulfated Cu-CHA SCR catalysts is severely degraded at evaluation temperatures below 250 • C; however, above 250 • C the impact of sulfur exposure is minimal. EPMA sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 30 publications
(47 reference statements)
3
28
0
2
Order By: Relevance
“…The formation of CePO 4 in aged TWCs has been reported in previous studies and has been clearly observed in this study when aging with ZDDP. Elsewhere, Larese et al [18] investigated the contaminants present in a TWC aged under real working conditions of ca. 30,000 km, and demonstrated the formation of CePO 4 in the aged catalyst with the aid of XRD.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of CePO 4 in aged TWCs has been reported in previous studies and has been clearly observed in this study when aging with ZDDP. Elsewhere, Larese et al [18] investigated the contaminants present in a TWC aged under real working conditions of ca. 30,000 km, and demonstrated the formation of CePO 4 in the aged catalyst with the aid of XRD.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration of the upstream particulate filter can also lead to a high temperature exhaust and oxygen depletion. 9 The effects of hydrothermal aging, [10][11][12][13][14][15][16] sulfur exposition and regeneration [17][18][19] have been studied to better understand the aging mechanism under practical operating conditions. Collapse of the zeolite structure, active metal agglomeration and dealumination are the most common identified aging mechanisms that occur during thermal aging.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrates and adsorbed NO 2 were formed on the surface of the catalyst as attested by the absorption bands in the region 1500-1700 cm −1 on all catalysts (not shown). A broad and intense feature, composed of three peaks at 2213, 2183, and 2158 cm −1 , was found on degreened and aged catalysts at 800 • C. These peaks were assigned to NO + in cationic sites (2158 cm −1 ) and NO + NO 2 adducts (2213, 2183 cm −1 ) [34,35]. A less intense band, attributed to NO adsorbed on isolated Cu 2+ [20,36,37], was found in the 1850-1950 cm −1 region.…”
Section: No Adsorption On Oxidized Cu/ssz-13mentioning
confidence: 98%